The norepinephrine transporter gene is associated with the retardation symptoms of major depressive disorder in the Han Chinese population - Li, Xinrong; Sun, Ning; Xu, Yong; Wang, Yanfang; Li, Suping; Du, Qiaorong; Peng, Juyi; Luo, Jinxiu; Zhang, Kerang (Neural regeneration research, 2012)
The norepinephrine transporter plays an important role in the pathophysiology and pharmacological treatment of major depressive disorder. Consequently, the norepinephrine transporter gene is an attractive candidate in major depressive disorder research. In the present study, we evaluated the depression symptoms of subjects with major depressive disorder, who were all from the North of China and of Hart Chinese origin, using the Hamilton Depression Scale. We examined the relationship between two single nucleotide polymorphisms in the norepinephrine transporter, rs2242446 and rs5569, and the retardation symptoms of major depressive disorder using quantitative trait testing with the UNPHASED program, rs5569 was associated with depressed mood, and the GG genotype may be a risk factor for this; rs2242446 was associated with work and interest, and the TT genotype may be a risk factor for loss of interest. Our findings suggest that rs2242446 and rs5569 in the norepinephrine transporter gene are associated with the retardation symptoms of depression in the Hart Chinese population.